Thermochemical reaction characteristics of degradable active materials under high temperature conditions. (19th March 2022) - Yang, Xuewen
Aiming at the problems of poor emulsification and slow heat release of traditional degradable active materials, the thermochemical reaction characteristics of degradable active materials at high temperature were studied. The relationship between temperature and permeability index and diffusion index of degradable active materials was defined by Arrhenius equation, and the thermal degradation concentration decline model and viscosity decline model were constructed. The standard equilibrium constants of each stage of the decomposition reaction of the degradable active materials were used to obtain accurate degradation performance test results. The results show that at 150°C, the particle size of the material is smaller, the distribution is uniform, and it has good emulsifying performance. When the temperature reached about 100°C, the maximum emulsification rate of the material reached 56.64 ml/min -1 . The peak values of heat release rate were 714.5 kw/m 2 and 524.6 kw/m 2 respectively, which were lower than those of natural rubber.